Caracterização dos fatores de risco biomecânicos, individuais e psicossociais em trabalhadores de uma empresa de manutenção de automóveis - Arêdes, Thaís Benicá (2015)
Introduction: Car maintenance workers who perform the handling of loads have been particularly affected by musculoskeletal disorders related to work, as they are exposed to various risk factors, being the backbone of the most affected region. Among the ergonomic risk factors, the extreme positions have been known to show association with the development of musculoskeletal injuries and can be quantified by inclinometry. Furthermore, the individual risk factors, and psychosocial factors are associated with the development of musculoskeletal symptoms related to work. Objective: To characterize the biomechanics, individual and psychosocial risk factors that workers of a car maintenance company are exposed. Methodology: The study involved 36 workers workshop sectors (mechanics, plumbers and accessories installers) and pieces, which responded to the initial questionnaire, to identify the participants; the Nordic questionnaire for evaluation of symptoms; the Roland Morris questionnaire to assess functional capacity, the WHOQOL-BREF questionnaire to assess quality of life and of the Job Stress Scale (JSS). In addition, they underwent clinical evaluation and assessment by inclinometry, which allowed measuring the posture and spine movement during the workday. Results: The results show that all workers were male and usually young (mean 32.6 ± 3.2 years). There were absences for health reasons in all evaluated sectors and as regards the presence of pain, the mechanical sub-sector (44.4%) and stock (85.7%) had a higher prevalence. The most affected body regions were wrists / hands and lower back between the mechanical and wrists / hands and the top and bottom of the back between the tinkers, as for installers of accessories, the highest prevalence of symptoms was in the upper region of back and stockists between the lower back and knees. Regarding functional evaluation, no individual was identified with limitation. For the overall quality of life, the perception of quality of life was rated as good for the mechanics and installers accessories, but not to the tinkers and stockists, which were classified as regular. For the physical, psychological, social, mechanics, plumbers and accessories installers perceive their quality of life as good, as stockists as regular. In relation to the environment, all workers classify the quality of life as regular. Considering the stress at work, in general, workers showed perception of high demand, control and social support. With regard to percentiles posture and movements of the spine, there was no significant difference between sectors, but there were differences between task and break. It was also identified differences between sectors and between task and break angular velocity. Conclusion: It was found that the posture adopted by automobile maintenance workers exposes risks for the development of musculoskeletal disorders of the spine, and that the individual and psychosocial risk factors may also contribute to the development of these disorders. It also highlights the need for more studies with this approach.